Deformation Analysis and Prediction of Foundation Pit in Soil-Rock Composite Stratum - Qin, Zehong; Tao, Zhe; Chen, Zechao; Zhang, Ziguang; Tang, Chuangao; Liu, Hao; Ren, Quan (Frontiers in Physics, 2022)
The deformation prediction of foundation pit is still an open issue in geotechnique engineering. This paper focuses on a new deformation prediction method of foundation pit in soil-rock composite stratum in Nanjing area. To do so, the field monitoring deformation data of deep foundation pit adjacent to the railway in a soil-rock combined stratum is firstly analyzed. Based on these field data, the characteristics of horizontal displacement and surface settlement of rock-socketed support pile, as well as its relationship with earth excavation are discussed. Results show that the average value of maximum horizontal displacement of support pile in zone with shallow rock depth (soil layer > 15m) is relatively large, which is 3.5 times of that with shallow soil depth (10m-12m into moderately-weathered mudstone). The depth of maximum horizontal displacement is obviously linearly related to the thickness of soil layer(H)，while the surface settlement does not change with the increase of soil/rock layer thickness ratio. Utilizing the relationship between the maximum water level displacement and excavation depth, a new Gaussian-type empirical formulation is established to predict horizontal deformation of soil-rock composite stratum with rock-socketed support pile. By comparison with two other methods, it is found that the improved Gaussian curve is in good agreement with the measured horizontal displacement curve. This indicates that the new method can provide a valid reference for the design and construction of foundation pit with rock-socketed support pile in Nanjing area.